Handbook on Native American justice issues - French, Laurence (Routledge handbooks, 2019)
"Bringing together contributions from leading scholars--many of them Native Americans--that explore key issues fundamental to understanding the relationships between Native peoples and contemporary criminal justice, editor Laurence Armand French draws on more than 40 years of experience with Native American individuals and groups to provide contextual material that incorporates criminology, sociology, anthropology, cultural psychology, and history to give readers a true picture of the wrongs perpetrated against Native Americans and their effects on the current operation of Native American justice. This compilation analyzes the nature of justice for Native Americans, including unique and emerging problems, theoretical issues, and policy implications. It is a valuable resource for all scholars with an interest in Native American culture and in the analysis and rectification of the criminal justice system's disparate impact on people of color"--